Nigerian students' perceptions of academic departments as a teaching and learning environment (2002)
This study examined the quality of the academic environment in tertiary institutions in Nigeria from the perspective of undergraduate students. The sample consisted of 348 final-year students of mathematics, chemistry, english, economics and education at the University of Ibadan, Ilorin and Ogun state. Distanct academic cultures were apparent in different departments. Lecturers in the natural sciences were formal with their students and had a strong influence on thier intellectual development. In the social sciences and arts they were more 'businesslike' but less committed and poor at meeting students' academic needs. Education lecturers were less formal but gave less academic guidance. The differences reflected the amount of personal attention and academic guidance students got and thier relations with the lecturers. All resented being expected to be wholly commited when their teachers were not. Relations between teachers and taught could be a lot better. Most students have some choice of what to learn and how. Students like to have a voice in decision that affect tham and would be more committed in their work if help were more readily available and their efforts were more appreciated